Computer and Internet use by persons after traumatic spinal cord injury. - Goodman N; Jette AM; Houlihan B; Williams S (Archives of Physical Medicine & Rehabilitation, 2008)
OBJECTIVE: To determine whether computer and internet use by persons post spinal cord injury (SCI) is sufficiently prevalent and broad-based to consider using this technology as a long-term treatment modality for patients who have sustained SCI. DESIGN: A multicenter cohort study. SETTING: Twenty-six past and current U.S. regional Model Spinal Cord Injury Systems. PARTICIPANTS: Patients with traumatic SCI (N=2926) with follow-up interviews between 2004 and 2006, conducted at 1 or 5 years postinjury. INTERVENTIONS: Not applicable. RESULTS: Results revealed that 69.2% of participants with SCI used a computer; 94.2% of computer users accessed the internet. Among computer users, 19.1% used assistive devices for computer access. Of the internet users, 68.6% went online 5 to 7 days a week. The most frequent use for internet was e-mail (90.5%) and shopping sites (65.8%), followed by health sites (61.1%). We found no statistically significant difference in computer use by sex or level of neurologic injury, and no difference in internet use by level of neurologic injury. Computer and internet access differed significantly by age, with use decreasing as age group increased. The highest computer and internet access rates were seen among participants injured before the age of 18. Computer and internet use varied by race: 76% of white compared with 46% of black subjects were computer users (P<.001), and 95.3% of white respondents who used computers used the internet, compared with 87.6% of black respondents (P<.001). Internet use increased with education level (P<.001): eighty-six percent of participants who did not graduate from high school or receive a degree used the internet, while over 97% of those with a college or associate's degree did. CONCLUSIONS: While the internet holds considerable potential as a long-term treatment modality after SCI, limited access to the internet by those who are black, those injured after age 18, and those with less education does reduce its usefulness in the short term for these subgroups. Copyright © 2008 by the American Congress of Rehabilitation Medicine and the American Academy of Physical Medicine and Rehabilitation